2008
DOI: 10.1128/aac.01403-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection and Characterization of Ceftobiprole-Resistant Methicillin-Resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is resistant to ␤-lactam antibiotics because it expresses penicillin-binding protein 2a (PBP2a), a low-affinity penicillin-binding protein. An investigational broadspectrum cephalosporin, ceftobiprole (BPR), binds PBP2a with high affinity and is active against MRSA. We hypothesized that BPR resistance could be mediated by mutations in mecA, the gene encoding PBP2a. We selected BPR-resistant mutants by passage in high-volume broth cultures containing subinhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 26 publications
2
66
0
1
Order By: Relevance
“…Se postularon tres mecanismos involucrados en la resistencia in vitro: la inhibición de la unión al substrato, la interferencia de la interacción proteína-proteína y la inhibición de la acilación. También se detectó resistencia en cepas que no presentaban el gen mecA y que, por lo tanto, no expresaban la proteína, por lo que se postuló que otros genes cromosómicos tendrían efecto en la resistencia a ceftobiprol (142).…”
Section: Resistencia a Cefalosporinas De úLtima Generaciónunclassified
“…Se postularon tres mecanismos involucrados en la resistencia in vitro: la inhibición de la unión al substrato, la interferencia de la interacción proteína-proteína y la inhibición de la acilación. También se detectó resistencia en cepas que no presentaban el gen mecA y que, por lo tanto, no expresaban la proteína, por lo que se postuló que otros genes cromosómicos tendrían efecto en la resistencia a ceftobiprol (142).…”
Section: Resistencia a Cefalosporinas De úLtima Generaciónunclassified
“…Our laboratory previously reported the emergence of ceftobiprole-resistant MRSA in vitro (1). We demonstrated that serial passage of MRSA strain COL in subinhibitory ceftobiprole concentrations selected for point mutations in mecA that conferred resistance to ceftobiprole and other ␤-lactams.…”
mentioning
confidence: 98%
“…COLnex was transformed with a plasmid vector, pAW8, and serially passaged in increasing concentrations of ceftobiprole and 10 g/ml of tetracycline as previously described (1). A resistant mutant, CRB, was selected after 21 days of serial passage in ceftobiprole; MICs increased from 1 for the COL parent to 256 g/ml for mutant strain CRB.…”
mentioning
confidence: 99%
“…Ceftobiprole has been evaluated in clinical trials, and ceftaroline is FDA approved for treat-ment of skin and skin structure infections, including those caused by MRSA (5)(6)(7)(8)(9)(10). Previous studies from our group have shown that passage of the COL strain in ceftobiprole selects for resistant mutants with mutations in PBP2a (11). This study examines whether ceftaroline passage also selects for similar mutations.…”
mentioning
confidence: 99%
“…It is present in ceftobiprole-passaged COL (among other mutations) (11), it is the only mecA mutation in the ceftaroline-passaged SF8300, and it has been reported in clinical isolates (17,18). Structurally, E447 resides in the penicillin-binding domain of PBP2a and interacts with the R2 group of ceftobiprole and other ␤-lactams (3, 19).…”
mentioning
confidence: 99%